MANAJEMEN INVESTASI DAN PROTEKSI KEKAYAAN PADA BAPAK MARSUDI - , Miqdam Roidal Haq ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Needs of wealth management has increased along with the increasing number of high net worth investor. The main purpose of wealth management is to increase wealth and protect wealth possessed of risk that will happen. Both of these are important aspects to consider in order to achieve the financial goals of investors. This study aims to formulate recommendation related to wealth management client in terms of investment and wealth protection. Client in this study has a very aggressive of risk taking in investment. Recommendation related to investment assets consist of two scenarios that are adjusted to the type of client risk, and recommendation related to the protection just a scenario. The study recommend that the client needs to add some insurance of staying home insurance, motor insurance, and investment diversification as a strategy to protect the client investment asset. Recommendation related to investment asset was done by adding a mutual fund investment assets, real business, and commodities.